Dietary supplement of mushrooms promotes SCFA production and moderately associates with IgA production: A pilot clinical study - Nishimoto, Yuichiro; Kawai, Junya; Mori, Koichiro; Hartanto, Tenagy; Komatsu, Kaori; Kudo, Toru; Fukuda, Shinji (Frontiers in Nutrition, 2023)
Background: Mushrooms are rich in dietary fiber, and fiber intake has been reported to increase the levels of short-chain fatty acids (SCFAs). It has also been reported that SCFAs promote immunoglobulin A (IgA) production, indicating involvement in systemic immunity. Objectives: The objective of this study was to evaluate the effects of mushroom consumption on the amount of intestinal IgA. We also aimed to comprehensively evaluate the gut microbiota and intestinal metabolome and to conduct an exploratory analysis of their relationship with IgA. Methods: Healthy adults (n = 80) were enrolled in a parallel group trial. Participants consumed a diet with mushrooms or a placebo diet once daily for 4 weeks. Gut microbiota profiles were assessed by sequencing the bacterial 16S ribosomal RNA-encoding gene. Intestinal metabolome profiles were analyzed using capillary electrophoresis-time of flight mass spectrometry (CE-TOFMS). Results: Mushroom consumption tended to increase IgA levels at 4 weeks of consumption compared to those in the control group (p = 0.0807; Hedges’ g = 0.480). The mushroom group had significantly higher levels of intestinal SCFAs, such as butyrate and propionate, than the control group (p = 0.001 and 0.020; Hedges’ g = 0.824 and 0.474, respectively). Correlation analysis between the changes in the amount of intestinal IgA and the baseline features of the intestinal environment showed that the increasing amount of intestinal IgA was positively correlated with the baseline levels of SCFAs (Spearman’s R = 0.559 and 0.419 for butyrate and propionate, respectively). Conclusions: Consumption of mushrooms significantly increased the intestinal SCFAs and IgA in some subjects. The increase in intestinal IgA levels was more prominent in subjects with higher SCFA levels at baseline. This finding provides evidence that mushroom alters the intestinal environment, but the intensity of the effect still depends on the baseline intestinal environment. This trial was registered at www.umin.ac.jp as UMIN000043979.